Palbociclib with letrozole as second-line neo-systemic therapy after failure of neo-adjuvant chemotherapy for luminal type breast cancer: A case report. Issue 14 (9th April 2021) - Jung, Sung Ui; Jung, Minjung; Choi, Jin Hyuk; Jeon, Chang Wan
Abstract: Rationale: Neo-adjuvant systemic therapy includes endocrine therapy and chemotherapy, which is widely used. Luminal breast cancer is resistant to chemotherapy and is more likely to not respond to chemotherapy before surgery. Palbociclib is a cyclin-dependent kinase 4 and 6 inhibitor. Palbociclib with letrozole combination therapy was an effective chemotherapy in metastatic luminal type breast cancer and had fewer side effects; however, the benefit of palbociclib in neoadjuvant systemic therapy is unclear. Patient concerns: A 50-year-old female patient visited our hospital with palpable lump in the right breast. The lymph nodes fixed in the ipsilateral axilla. Diagnosis: The patient was diagnosed with invasive ductal carcinoma of the right breast; the nuclear grade was moderate. The ipsilateral fixed lymph node was diagnosed as metastasis. The breast cancer subtype was luminal A type and was positive for estrogen receptor and progesterone receptor, and negative for HER2/neu and Ki-67 marker index <10% on immunohistochemistry. Interventions: Neo-systemic therapy was performed with 3 cycles of adriamycin with docetaxel. After follow-up study, the breast and axillary lesions progressed. Palbociclib with letrozole was administered as second neo-systemic therapy for 10 months. Subsequently, breast-conserving surgery with sentinel lymph node biopsy was performed. Outcomes: In the postoperative pathologic result, 4 mm invasive lesion remained, and the sentinel lymph node biopsy was negative. The results achieved a residual cancer burden classification class 1. Conclusion: Second-line neo-systemic therapy can further reduce the size of the tumor and increase the likelihood of avoiding the side effects of surgery. Palbociclib with letrozole may be a good treatment in the preoperative stage for luminal breast cancer that is resistant to chemotherapy.